Leptocephali collected off the eastern coast of Brazil (12°–23°S) - de Castro, Márcia Salustiano; Bonecker, Ana Cristina Teixeira (Zootaxa, 2005)
Although leptocephali are very conspicuous in plankton samples little is known about their occurrence and distribution along the Brazilian coast. Therefore, the present study aimed to identify the leptocephali and their distribution pattern along the eastern Brazilian coast, which is limited in the north by Real River (12°S) and in the south by São Tomé Cape (23°S). Samples were collected during three oceanographic cruises conducted on October–December 1998, May–July 1999 and March–May 2000. Samplings were done using a bongo net with mesh apertures of 330 and 500 µm. The net was towed obliquely and the maximum depth was 200 m. A total of 13 families, 12 genera and 29 species of leptocephali were identified in the study area. Most taxa identified had already been recorded as adult, but the larval phase of some of them had not been identified for this region yet. Among them, Derichthyidae, Avocettina paucipora and Tiluropsis had not been recorded for this region either as adult or as larvae. Most taxa occurred mainly along the Bahia coast but some species were collected strictly in the southern region of the study area.